La mémoire blessée des Juifs du M'zab - Raphaël, Freddy (Communautés juives des marges sahariennes du Maghreb, 1982)
Keywords: Judaïsme – Mzab

Réflexions sur la symbiose judéo-ibadite en Afrique du Nord - Shinar, Pessah (Communautés juives des marges sahariennes du Maghreb, 1982)
A kind of anthropological comparison between Jews and Ibāḍīs in Mīzāb. Shinar concludes: Mīzāb offers us an example of a rare coexistence of two ethnic-socio-cultural isolated groups of people, inequal in numbers and status, which have purely functional contacts. Living closely together, they present notable similarities, but also numerous and profound differences. The Ibāḍīs base their way of life on the Koran, the Tradition, and the Ibāḍī theology, jurisprudence and ethics, with a Berber-Zenati substrate; the Jews base theirs on the Talmudic and mystical biblical tradition, as well as on their ancient Mālikite, especially Moroccon, environment. Both groups, looking outwardly fossilized, have in them the germs of renewal, that orientate the Ibāḍīs towards an oriental renaissance, al-Nahḍa, and the reformism of the orthodox Salafiyya, while the other group, in their exodus, are directed towards Israel and France.
Keywords: Judaïsme – Mzab

La "nation juive" de Ghardaïa - Goutalier, Régine (Communautés juives des marges sahariennes du Maghreb, 1982)
Keywords: Judaïsme – Mzab